Kepatuhan Penerapan Prokes Pada Proses Pendaftaran Paslon Bupati Mojokerto Tahun 2020: Proses Pendaftaran Paslon Bupati Mojokerto Tahun 2020 - Faculty of Social and Political Sciences, Majapahit Islamic University, Mojokerto, Suprapto; English Language Study Program, Faculty of Teacher Training and Education. Majapahit Islamic Univers; Faculty of Social and Political Sciences, Majapahit Islamic University, Mojokerto, Ahmad Hasan Afand (MAJAPAHIT POLICY, 2021)
The biggest challenge in implementing simultaneous local elections during a pandemic is the level of compliance with health protocols. Candidate participantsPilkada that has a mass basis is certainly an important spotlight for compliance with the implementation of health protocols. Commitment of election participants in various regionsRegions including Mojokerto Regency will certainly be very significant in suppressing the spread of Covid-19. This research aims todescribes the level of compliance of the Mojokerto Regent candidate pair for the 2020-2025 period in implementing health protocols at the time of registration at the KPU.By considering various regulations related to health protocols during a pandemic, the description in this study covers the general pictureregent candidate registration activities, the stages of registration, as well as the compliance of regent candidate pairs in carrying out health protocols. Research Typewhich is used in this study is to use a qualitative descriptive type of research where the basis of this research is interviews, namelyconducting dialogues (interviews) with informants with questions related to research.The results of the study show that from the entire registration process, all candidate pairs have carried out various stages by implementing the protocolhealth in a disciplined manner. Likewise with the organizers, all the rules given to the candidate pairs are designed so that there are no loopholesCovid-19 transmission. The Mojokerto Regency KPU was successful in carefully socializing the health protocol regulations to each candidate pair.However, there are dynamics in the nomination process, especially at the registration stage, including delays in collecting resultsswab and the procession before the registration process